Chemoenzymatic synthesis of 6‐phospho‐cyclophellitol as a novel probe of 6‐phospho‐β‐glucosidases. Issue 4 (14th February 2016) - Kwan, David H.; Jin, Yi; Jiang, Jianbing; Chen, Hong‐Ming; Kötzler, Miriam P.; Overkleeft, Herman S.; Davies, Gideon J.; Withers, Stephen G.
Abstract : Covalent, mechanism‐based inhibitors of glycosidases are valuable probe molecules for visualizing enzyme activities in complex systems. We, here, describe the chemoenzymatic synthesis of 6‐phospho‐cyclophellitol and evaluate its behaviour as a mechanism‐based inactivator of the Streptococcus pyogenes 6‐phospho‐β‐glucosidase from CAZy family GH1. We further present the three‐dimensional structure of the inactivated enzyme, which reveals the constellation of active site residues responsible for the enzyme's specificity and confirms the covalent nature of the inactivation. Abstract :